6102 sayılı TTK uyarınca limited şirketin sona ermesi - Çiltaş, Nurve (My University, 2022)
Türk Ticaret Kanunu ile birlikte, limited şirket kanun koyucu tarafından önceki düzenlemelere kıyasla farklı ele alınmıştır. Günümüzde limited şirketin serbest piyasada gelmiş olduğu konum itibariyle artan önemi doğrultusunda karma özelliğe sahip şirket yapısından dönülmüş ve limited şirket sermaye şirketi olarak kanunda açıkça düzenlenmiştir. Şirketin kuruluşu kadar, sona ermesine ilişkin hüküm ve sonuçlarının üçüncü kişiler nezdinde doğuracağı etkilerinin de oldukça önemli olması sebebiyle kanun koyucu tarafından şirketi sona erdiren sebepler de ayrıca TTK m.636 ile tek tek düzenlenmiştir. Bu kapsamda sözleşmede yazılı sebepler, şirket genel kurul kararı, şirketin iflası ve kanunda öngörülen diğer sebepler olarak sıralanmıştır. Ayrıca ortaklar, şirket sözleşmesinde kanuna aykırı olmamak koşulu ile başkaca sona erme sebeplerine de yer verebilirler. Nitekim, TMK hükümleri doğrultusunda da şirketin mahiyetine uygun olması koşulu ile şirketin tüzel kişiliğini sona erdiren sebepler de uygulanabilir. Limited şirket her ne kadar anonim şirkete benzer olarak düzenlenmiş olsa da, mahiyeti itibariyle farklılık arz eden noktaları ve anonim şirketten ayrılan yönleri sebebiyle sona ermesine ilişkin hüküm ve sonuçlarının daha detaylı ele alınması gerekir. Zira, piyasa nezdinde oldukça önemli bir yere sahip olan limited şirketin müdür ve ortaklarının şirket borçlarından sorumluluğu noktasında anonim şirketinden ayrılan yönleri ticari hayatta önem arz etmektedir. Bu kapsamda, sona erme sebeplerinden birinin gerçekleşmesi ile birlikte tasfiye aşamasına giren şirket, tasfiye işlemlerinin tamamlanmasının akabinde sicilden kaydının silinmesiyle hukuki varlığı sona erer. Nitekim, şirketin sona ermesinin son çare olması ilkesi doğrultusunda kanun koyucu tarafından şirketin sona erdirilmesini önleyebilecek konkordato, borçların yapılandırılması vb. mekanizmalar getirilmiş, şirketin ayakta tutulmasına öncelik tanımıştır. Ayrıca, gerekli koşulların oluşması halinde şirketin tekrardan canlandırılıp eksik kalan tasfiye işlemlerinin tamamlanabilmesini sağlayan ek tasfiye kurumu da mevzuatımıza kazandırılmıştır.

With the Turkish Commercial Code, the limited company has been handled differently by the legislator compared to the previous regulations. Today, in line with the increasing importance of the limited company due to its position in the free market, the company structure with mixed characteristics has been reversed and the limited company has been clearly regulated in the law as a capital company. The reasons for the termination of the company by the lawmaker are also regulated one by one with article 636 of the TCC, as the effects of the provisions and consequences of the termination of the company on the third parties are as important as the establishment of the company. In this context, the reasons written in the contract are listed as the general assembly decision of the company, the bankruptcy of the company, and other reasons stipulated in the law. In addition, the partners may include other reasons for termination in the articles of association, provided that they are not against the law. As a matter of fact, in line with the provisions of the TMK, the reasons that terminate the legal personality of the company can also be applied, provided that it is suitable for the nature of the company. Although a limited liability company is regulated as a joint stock company, the terms and consequences of its dissolution should be dealt with in more detail due to its differences in nature and aspects that differ from the joint stock company. Because, the aspects of the limited company, which has a very important place in the market, differ from the joint stock company in terms of the liability of the directors and partners of the company's debts, are important in commercial life. In this context, the company, which entered the liquidation phase with the realization of one of the reasons for termination, ends its legal existence with the deregistration of the company following the completion of the liquidation procedures. As a matter of fact, in line with the principle that the termination of the company is the last resort, concordat, restructuring of debts, etc., which can prevent the termination of the company by the legislator. mechanisms were introduced and priority was given to keeping the company afloat. In addition, an additional liquidation institution, which enables the company to be revived and complete the incomplete liquidation transactions, has been added to our legislation if the necessary conditions are met.
Keywords: Additional Liquidation; Auditing; Business enterprises; Corporation law; Corporations; Denetim; Dissolution and Termination Cases; Ek Tasfiye; Expiration of the company; İnfisah ve Fesih Halleri; Law and legislation; Limited Şirket; Liquidation of the Company; Sicilden Terkin Limited Liability; Sona Erme; Şirket hukuku --Türkiye; Şirketin Tasfiyesi; Şirketler; Ticari teşebbüsler; Turkey; Türkiye; Withdrawal from Registry; Yasa ve yasama